Modelling Development in Plant Anatomy - Robert W. Korn (Journal of Advances in Plant Biology, 2018)
Four rules for good anatomical modeling of plants are explored. First, the cell is the reference source for modelling at any level. Second, developmental signaling occurs between few cells, about 12. Third, rules of are algorithmic and not simply physical forces as proposed by Thompson. Finally, it is desirable to proposed a likely alternative model that can be discounted. The main value of modelling is selecting data for modelling rather than the by a biased investigator.
Keywords: structural hierarchy